Judicial Psychiatry In China And Its Political Abuses - Munro, Robin (Columbia Journal of Asian Law, 2000)
This study does not claim to be a comprehensive analysis of the political aspects and abuses of Chinese forensic psychiatry. Many important questions remain to be considered elsewhere and by other observers, many of whom will doubtless be better qualified than this writer to comment on matters relating to lav and psychiatry. What follows is a preliminary attempt to bring together a significant corpus of new, though sometimes fragmentary, documentary evidence about the theory and practice of Chinese forensic psychiatry since 1949. It is one that amounts, however, to a clear and unmistakable prima facie case showing the longstanding and continuing existence of political psychiatric abuse in China.